Die französischen Übersetzungen von Kafkas Prozess - Jell, Anna (Studien des Interdisziplinären Frankreich-Schwerpunkts der Universität Innsbruck, 2012)
The siting of the novel The process in the French book trade is not without a certain Kafkaesque note: To date, five different versions of Kafka's perhaps most famous work are available in French. Kafka in France - the translations and the subsequent interpretations provide the reader not only a range of intellectual currents in France, but enable him to look at Kafka's works under the most varied points of view. The present work deals with the process, its genesis, distribution and reception of various French translations.